The Effect of Flipped Classroom Strategy on Students Learning Outcomes - Jdaitawi, Malek (International Journal of Instruction, 2019)
The purpose of this study is to examine the effects of the flipped classroom strategy to preparatory year instruction on student's self-regulation and social connectedness. A quasi-experimental pre-post-test design conducted with 160 university students enrolled in three educational tracks (health, engineering and science). The students were divided into two groups: an experimental flipped classroom group and a control group. Experimental group was taught via flipped classroom, while the control group taught via traditional strategy. The levels of self-regulation and social connectedness were measured through questionnaire at the beginning and the end of the classes. The results based on ANOVA analysis reported that students in flipped classroom had shown significantly higher level of self-regulation and social connectedness compared to students in the traditional group. Based on the obtained findings, self-regulated learning and social connectedness were successful in making significant improvements among students exposed to flipped classroom mode compared to their counterparts in the traditional group. The results demonstrate that flipped classroom strategy can be used to promote self-regulated learning and enhancing students' social connectedness.